2018
DOI: 10.1108/jgm-08-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Expatriation, alcohol and drugs: antecedents and consequences of substance use in expatriation

Abstract: Purpose Expatriation is known to be stressful. The purpose of this paper is to examine stress as an antecedent of substance use (SU) during expatriation and related effects on expatriates’ work adjustment. Moreover, the study sheds light on individual-level moderators (i.e. gender and prior international experience) and organizational-level moderators (i.e. organizational social support) that might condition the stress–SU link. Design/methodology/approach This work adopts a quantitative survey approach. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
0
12
1
1
Order By: Relevance
“…To explain how severe crisis events might occur for expatriates, we position them as arising primarily from acculturation stress or behavioural maladjustment, including contextual or cultural lack of knowledge, ignorance and incompetence as well as inappropriate emotional reactions caused by acculturation stress (cf. Fee et al, 2013;Fee et al, 2017;Turner & Pidgeon, 1997;Nolan & Morley, 2014;Wurtz, 2018). In our model, which is depicted in Figure 1, acculturation stress and/ or behavioural maladjustment are outcomes arising from triggers in the 'domains of causes'.…”
Section: Defining Fit-dependent Expatriate Crisesmentioning
confidence: 99%
See 4 more Smart Citations
“…To explain how severe crisis events might occur for expatriates, we position them as arising primarily from acculturation stress or behavioural maladjustment, including contextual or cultural lack of knowledge, ignorance and incompetence as well as inappropriate emotional reactions caused by acculturation stress (cf. Fee et al, 2013;Fee et al, 2017;Turner & Pidgeon, 1997;Nolan & Morley, 2014;Wurtz, 2018). In our model, which is depicted in Figure 1, acculturation stress and/ or behavioural maladjustment are outcomes arising from triggers in the 'domains of causes'.…”
Section: Defining Fit-dependent Expatriate Crisesmentioning
confidence: 99%
“…Lu et al (2017) found that the frequency of relocations (breadth) rather than the length of stay in any one location (depth) was a positive predictor of immoral behaviour. Studies (e.g., Lu et al, 2017;Wurtz, 2018) have thus concluded that it is not whether the host country is more or less moral than one's home country that matters (e.g., corruption, crime), but the number of foreign experiences one is exposed to. It suggests that when expatriates engage in frequent relocations abroad, they are more likely to experience moral relativism arising from "appreciating the differences in moral beliefs upheld by different cultures" (p. 13).…”
Section: The Personal Domainmentioning
confidence: 99%
See 3 more Smart Citations